The Difference of C-Reactive Protein Levels in Acute Fever causedby Dengue and Typhoid Infections - Idhayu, Adeputri Tanesha; Chen, Lie Khie; Suhendro, Suhendro (UI Scholars Hub, 2016)
Introduction. Dengue infection and typhoid fever are endemic disease in Indonesia. But in the early days of onset sometimes it is difficult to distinguish them. A simple modality test is needed to support the diagnosis. C-Reactive Protein (CRP) is an affordable, fast and relatively less expensive diagnostic tool to diagnose the causes of acute fever. This study was aimed to determine the differences of CRP level in the acute febrile caused by dengue infection or typhoid fever. Methods. A cross sectional study has been conducted among acute febrile patients with diagnosis of dengue fever/ dengue hemorrhagic fever or typhoid fever who admitted to the emergency room or hospitalized in Cipto Mangunkusumo Hospital, Pluit Hospital, and Metropolitan Medical Center Hospital Jakarta between January 2010 and December 2013. Data obtained from medical records. CRP used in this study was examined at 2-5 days after onset of fever. The other collected data were demographic data, clinical data, use of antibiotics, leukocytes, platelets, neutrophils, ESR, and length of stay in hospital. Results. 188 subjects met the inclusion criteria; 102 patients with dengue and 86 patients with typhoid fever. Median CRP levels in dengue infection was 11.65 (16) mg/L and in typhoid fever was 53 (75) mg/L. There were significant differences in median CRP levels between dengue infection and typhoid fever (p < 0.001). At the 99% percentile cut-off point, CRP levels for dengue infection was 45.91 mg/L and CRP levels for typhoid fever at 1% percentile was 8 mg / L. Conclusions. There was significantly different levels of CRP in acute fever due to dengue infection and typhoid fever. At the 99% percentile cut-off point, CRP level >45.91 mg/L was diagnostic for typhoid fever, CRP level /L was diagnostic for dengue infection. CRP level between 8 to 45.91 mg/L was a gray area for determinating diagnosis of dengue infection and typhoid fever.